2018
DOI: 10.1111/pcn.12656
|View full text |Cite
|
Sign up to set email alerts
|

Association between iron‐deficiency anemia and depression: A web‐based Japanese investigation

Abstract: Self-reported history of iron-deficiency anemia was associated with self-reported history of depression. Furthermore, self-reported history of iron-deficiency anemia was associated with higher psychological distress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 35 publications
4
31
0
3
Order By: Relevance
“…In the Hidese et al . study a significant association was found between iron‐deficiency anemia and depression . In our study, iron in the diet reduced the risk of depression.…”
Section: Discussionsupporting
confidence: 64%
“…In the Hidese et al . study a significant association was found between iron‐deficiency anemia and depression . In our study, iron in the diet reduced the risk of depression.…”
Section: Discussionsupporting
confidence: 64%
“…A hospital-based case-control study with 100 cases and 100 controls showed a relationship between IDA and depressive disorder; and the severity of symptoms of depressive disorder increased with the degree of IDA [15]. A web-based survey, which consisted of 1,000 individuals and 10,876 controls, indicated that IDA was associated with a self-reported history of depression [26]. A case-control study which included 2,957 IDA patients and 11,828 healthy controls showed a higher risk of psychiatric disorders, including mood disorders, autism spectrum disorder, attention deficit hyperactivity disorder, and developmental disorders [14].…”
Section: Discussionmentioning
confidence: 99%
“…According to these criteria, anaemia is defined as haemoglobin levels below 13 g/L for men and below 12 g/L for women. In the remaining studies, anaemia was self-reported 25 26 or was defined according to tertiles of haemoglobin status 19 or bisection around the mean. 24…”
Section: Resultsmentioning
confidence: 99%